A structure and design optimization of novel compact microscrip dual‐band rat‐race coupler with enhanced bandwidth. Issue 10 (27th July 2016) - Bekasiewicz, Adrian; Koziel, Slawomir; Zieniutycz, Wlodzimierz
ABSTRACT: In the letter, a topology of a novel compact wideband dual‐band rat‐race coupler has been presented along with its computationally efficient design optimization procedure. Reduction of the circuit size has been achieved by meandering transmission lines of the conventional circuit. At the same time, the number of independent geometry parameters has been increased so as to secure sufficient flexibility of the circuit, necessary in the context of its design optimization for dual‐band operation. All relevant geometry parameters of the coupler have been obtained by means of automated simulation‐driven design optimization process involving surrogate‐based techniques. The operating frequencies of the coupler are 1 GHz and 2 GHz, whereas a −18 dB bandwidth is as wide as 22.5 and 11.3 percent for the lower and upper band, respectively. The miniaturization rate is over 37 percent compared to the conventional structure. The design is validated through full‐wave EM analysis at fine discretization as well as through physical measurements of the fabricated circuit prototype. © 2016 Wiley Periodicals, Inc. Microwave Opt Technol Lett 58:2287–2291, 2016